Produção textual: o gênero artigo de opinião através de sequências didáticas no ensino fundamental - Silva, Jacineide Virgínia Borges Oliveira da (2016)
This action research emerged from the observation of the increasingly satisfactory yield in the written productions of the students of the 9th grade of Elementary School of a public, state school, located in the city of Pedras de Fogo – PB. On this context, we aim to ameliorate such problems present in our school context. Some studies have shown new forms and methods for a more effective process of teaching-learning of textual production. In this way, our objective is to make the students competent producers of texts, starting from a proposal of teaching about the discursive genre called opinion article, through didactic sequences. Thus, having as theoretical foundation the contributions brought by Bakhtin (2003) about the conception of genres, as well as the contributions of other researchers such as: Cavalcante (2013), Geraldi (1996), Koch and Elias (2015) about the same thematic, and our proposal of intervention was based on the scheme of didactic sequence proposed by Dolz; Noverraz; Schneuwly (2004). The corpus of the research was composed by the initial and final textual productions of the students, in the case six (6) initial with six (6) final, totalizing twelve (12) productions of the genre opinion article. On the initial productions, we were able to detect some of the students' inadequacies regarding the structure, the level of information and also to the adequacy to the cultured norm of the Portuguese Language, related to the production of this discursive genre and that were worked during the intervention with the didactic sequence. After this stage, the students had the opportunity to rewrite their texts following the guidelines given by the teacher, in order to adapt the texts to the structure of opinion article described by the authors mentioned above. Finally, was evident the effectiveness of the implementation of the didactic sequence, which contributed significantly to the development of communicative skills of the students, more specifically with regard to the written production of the genre of opinion article.